Effect of foliar application of water soluble fertilizers on growth, yield and quality of tomato (Lycopersicon esculentum L.) - Subhash Kumar; Shakuntla Rahi; K.C. Sharma (Annals of Agricultural Research, 2023)
A study on the effect of water soluble fertilizers (WSF) on growth and yield parameters of tomato through on farm trials was carried-out in Mandi district of Himachal Pradesh during Kharif 2015 and 2016. The four treatments viz. T1 : Farmer's practice-12:32:16 @ 200 kg/ha and urea @ 100 kg/ha, T2 : FYM @ 20 t/ha + 100% NPK @ 125:100:60 kg/ha), T3 : 75% NPK + two foliar sprays each of NPK (17:44:0 & 0:0:50) T4 : 75% NPK + foliar application (three sprays of 18:18:18). The recommended doses of fertilizers (NPK) applied in combination with the water soluble fertilizers (WSF) in T3 resulted in a significant increase in growth parameters during both the years 2015 and 2016 viz. plant height 115.9 cm and 114.3 cm and number of branches 3.8 and 3.7 as compared with other treatments. Among yield attributes, a significant increase was observed during 2015 and 2016 in fruit weight 47.35 g and 46.87 g, yield per plant 3.31 and 3.34 kg during 2015 and 2016 and yield per ha were 351.5 and 349.5 q/ha, respectively. The net return of Rs. 5,41,215 with B:C ratio of 4.35 during 2015 and Rs. 536310 with B:C ratio of 4.31 during 2016 were obtained by applying the 75% NPK + two foliar sprays each of NPK (17:44:0 & 0:0:50) in T3 when compared with recommended dose of NPK and farmer practice, which can be recommended to the farmers and can give good returns.